(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
This article analyzes the expression of problems of finding equivalents in English and Uzbek idioms. In addition, the meaning of phraseologisms is considered along with the use of types and methods of idioms. It is very important to transfer expressions from the original language into the translated language while keeping a little meaning. It depends on the skill of the translator to give the translation of the phrases in their meaning, syntactic and morphological analysis and to provide alternative phrases corresponding to them in the Uzbek language. Therefore, in this article, we will consider the above-mentioned problems and their solutions.